Prolactin and its receptor as therapeutic targets in glioblastoma multiforme - Asad, Antonela Sofía (2019)
Although prolactin (PRL) and its receptor (PRLR) have been detected in glioblastoma multiforme (GBM), their role in its pathogenesis remains unclear. Our aim was to explore their contribution in GBM pathogenesis. We detected PRL and PRLR in all GBM cell lines tested. PRLR activation or overexpression using plasmid transfection increased proliferation, viability, clonogenicity, chemoresistance and matrix metalloproteinase activity in GBM cells, while PRLR antagonist ∆1–9-G129R-hPRL reduced their proliferation, viability, chemoresistance and migration. Meta-analysis of transcriptomic data indicated that PRLR was expressed in all grade II-III glioma (GII-III) and GBM samples. PRL was upregulated in GBM biopsies when compared to GII-III. While in the general population tumour PRL/PRLR expression did not correlate with patient survival, biological sex-stratified analyses revealed that male patients with PRL+/PRLRHIGH GBM performed worse than PRL+/PRLRLOW GBM. In contrast, all male PRL+/PRLRHIGH GII-III patients were alive whereas only 30% of PRL+/PRLRLOW GII-III patients survived after 100 months. Our study suggests that PRLR may be involved in GBM pathogenesis and could constitute a therapeutic target for its treatment. Our findings also support the notion that sexual dimorphism should be taken into account to improve the care of GBM patients.